1997
DOI: 10.1046/j.1365-201x.1997.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential titin isoform expression in human skeletal muscle

Abstract: Mammalian skeletal muscle expresses at least two isoforms of the cytoskeletal protein titin (connectin; MW approximately 3000 kDa). These isoforms are associated with different passive force curves, and thus may affect physical performance. To study the distribution of titin and its possible influence on performance in humans, muscle biopsies were obtained from 15 males (mean +/- SE; age = 25.4 +/- 2.9 years, height = 177.7 +/- 1.8 cm, weight = 76.5 +/- 2.2 kg). Two biopsies were obtained on separate occasions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…These results suggest that jumping exercise did not change titin isoform expression. Fry et al (1997) partly support this suggestion showing that each studied subject expressed the same titin isoforms in VL, GA, and SOL, and both a 16-week aerobic rowing and a 6-week sprint cycling training protocols did not appear to affect titin isoform composition. Toursel et al (2002) showed, however, that changes in passive tension could occur without changes in titin isoform expression in single fibers in unloaded rat SOL muscles.…”
Section: Discussionsupporting
confidence: 67%
“…These results suggest that jumping exercise did not change titin isoform expression. Fry et al (1997) partly support this suggestion showing that each studied subject expressed the same titin isoforms in VL, GA, and SOL, and both a 16-week aerobic rowing and a 6-week sprint cycling training protocols did not appear to affect titin isoform composition. Toursel et al (2002) showed, however, that changes in passive tension could occur without changes in titin isoform expression in single fibers in unloaded rat SOL muscles.…”
Section: Discussionsupporting
confidence: 67%
“…The question that arises from both this investigation and the study by Fry et al (1997) is to the true nature of these bands. Titin analysis through gel electrophoresis often results in two protein bands (Tatsumi and Hattori 1995).…”
Section: Discussionmentioning
confidence: 98%
“…1 Gel electrophoresis of human skeletal muscle using a 2% polyacrylamide gel reinforced with agarose for comparison of T1 and T2 relative quantities and relative mobilities between powerlifters, weightlifters, sprinters and nonathletes gation also reported that while some subjects expressed two titin protein bands others only expressed a single band. The study by Fry et al (1997) also examined preand post-titin band expression after an aerobic rowing and sprint cycling training protocol reporting no significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although from a single gene, the alternative splicing of titin mRNA allows for varying sizes of different titin isoforms to be present within striated muscle (45). In human skeletal muscle, two titin isoforms have been reported (62), with no fiber type-or muscle-specific associations observed (28). In both isoforms, the I-band region of titin is comprised of the proximal and distal immunoglobulin (Ig) tandem domains, the N2A domain, and a PEVK segment.…”
Section: Longitudinal Force Transmissionmentioning
confidence: 99%